Alumina aerogel modified polyester-based high-barrier adhesive tape and preparation method thereof
Patent Information
- Application Number
- CN202611043848.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-14
- Publication Date
- 2026-09-01
AI Technical Summary
[0013]本发明旨在克服现有技术中无机填料与有机胶粘剂相容性差、气凝胶易团聚破碎、高阻隔与柔韧性难以兼得等缺陷,提供一种氧化铝气凝胶改性聚酯基高阻隔胶带及其制备方法
[0039] Compared with the prior art, the present invention has the following beneficial effects:
Abstract
Description
Technical Field
[0001] This invention relates to the field of functional tape technology, and more specifically to an alumina aerogel-modified polyester-based high-barrier tape and its preparation method. Background Technology
[0002] With the rapid development of organic light-emitting diodes (OLEDs), quantum dot displays, flexible electronic devices, and high-efficiency photovoltaic modules, extremely stringent requirements have been placed on the water and oxygen barrier properties of encapsulation materials. An ideal encapsulation tape should have a water vapor transmission rate (WVTR) of less than 10%. -3 g / (m²·day) or even 10 -5 It is available in g / (m²·day) grade and also features excellent flexibility, weather resistance, optical transparency and strong adhesion to substrates.
[0003] Polyester film (especially PET) is widely used as a tape substrate due to its good mechanical strength, dimensional stability, and transparency. However, the barrier properties of unmodified PET-based tapes are far from meeting the requirements of high-end packaging—their WVTR is typically around 10. 0 Up to 10 1 It has a g / (m²·day) rating and a high oxygen permeability (OTR).
[0004] The existing technical approaches to improving barrier performance mainly include the following:
[0005] (1) Multilayer composite structure: Multilayer barrier films are prepared by alternating evaporation of inorganic oxide layers (such as Al2O3, SiO2) and organic buffer layers. This technology can achieve high initial barrier performance, but the process is complex and costly, and the inorganic layers are prone to microcracks when bent, which leads to a sharp decline in barrier performance.
[0006] (2) Nanosheet Filler Modification: Layered nanofillers, such as montmorillonite, graphene, and layered bimetallic hydroxides, are added to adhesives or coatings to extend the gas diffusion path by utilizing their high aspect ratio as a physical barrier. However, these fillers tend to agglomerate in the polymer matrix, and because their geometry is two-dimensional sheets, they only have an effective barrier effect perpendicular to the sheet direction, while there is a risk of diffusion "short circuit" in the parallel direction.
[0007] (3) Conventional nanoparticle filling: such as nano silica, alumina particles, etc., can improve the barrier properties to a certain extent, but a high filling amount (usually >20wt%) is required to form an effective permeation network. This will seriously degrade the flexibility and adhesion of the adhesive layer, and high filling will lead to decreased transparency and increased haze.
[0008] Alumina aerogel, as an ultralight material with a three-dimensional nanoporous network structure, theoretically provides extremely tortuous water and oxygen diffusion pathways, while also possessing thermal stability and chemical inertness. However, there are no reports of successful applications of alumina aerogel in high-barrier adhesive tapes in the current technology. The main technical obstacles are:
[0009] (i) The surface of alumina aerogel is rich in hydroxyl groups and is extremely polar. It has very poor compatibility with low-polarity polyurethane acrylate adhesive systems. Simple physical blending will lead to severe agglomeration, producing a large number of micron-sized aggregates, forming air gaps and defects, which in turn become channels for the rapid diffusion of water and oxygen.
[0010] (ii) The brittleness of aerogel itself makes it easy to break during tape bending or processing shearing, thus losing the integrity of the barrier structure;
[0011] (iii) There is currently no effective solution for controlling the orientation and distribution of aerogel in the adhesive layer so that it can form a three-dimensional barrier network without significantly increasing the internal stress of the adhesive layer.
[0012] Therefore, developing an alumina aerogel-modified polyester-based tape that combines ultra-high barrier properties, excellent flexibility, high transparency, and simple processing is a technical challenge that urgently needs to be solved in this field. Summary of the Invention
[0013] This invention aims to overcome the shortcomings of existing technologies, such as poor compatibility between inorganic fillers and organic adhesives, easy agglomeration and breakage of aerogels, and the difficulty in simultaneously achieving high barrier properties and flexibility. It provides an alumina aerogel-modified polyester-based high-barrier tape and its preparation method. By covalently grafting alumina aerogel with a surface modifier of a specific structure, combined with a modified polyurethane acrylate matrix of a specific composition and an optimized curing process, a complete three-dimensional nano-barrier network is constructed with a relatively low filler content, resulting in a simultaneous and significant improvement in water and oxygen barrier properties, mechanical flexibility, and optical transparency.
[0014] To solve the above-mentioned technical problems, this application adopts the following technical solution:
[0015] The primary objective of this application is to provide: an alumina aerogel-modified polyester-based high-barrier tape, the tape comprising a release layer, an adhesive layer, and a polyester substrate layer stacked sequentially;
[0016] The adhesive layer is prepared from raw materials comprising the following parts by weight:
[0017] 60-80 parts of modified polyurethane acrylate prepolymer;
[0018] 5-15 parts of coupling-modified alumina aerogel;
[0019] 15-30 parts of reactive diluent;
[0020] 1-5 parts of photoinitiator;
[0021] Additives: 0.5-2 parts;
[0022] The coupled-modified alumina aerogel is prepared by grafting γ-glycidyl etheroxypropyltrimethoxysilane onto alumina aerogel via a sol-gel surface reaction. The alumina aerogel has an average pore size of 10-50 nm and a specific surface area of 300-600 m². 2 / g. The epoxy groups of the silane coupling agent undergo ring-opening bonding with the hydroxyl groups on the aerogel surface, while epoxy functional groups are introduced on the aerogel surface. These epoxy groups can further react with the carboxyl or amino groups in the polyurethane acrylate prepolymer, or participate in the UV-cured crosslinking network through ring-opening polymerization, thereby achieving chemical bonding between the aerogel and the polymer matrix, rather than simple physical blending.
[0023] As a preferred technical solution, the coupling-modified alumina aerogel is prepared by the following method: alumina aerogel is dispersed in anhydrous ethanol, and 10-30% by weight of γ-glycidyl etheroxypropyltrimethoxysilane is added. The mixture is stirred and reacted at 60-80°C for 6-12 hours under nitrogen protection. After centrifugation, washing, and vacuum drying, the coupling-modified alumina aerogel is obtained.
[0024] As a preferred technical solution, the modified polyurethane acrylate prepolymer is prepared by the following method: polycarbonate diol, isophorone diisocyanate and hydroxyethyl acrylate with a number average molecular weight of 1000-3000 are reacted in the presence of the catalyst dibutyltin dilaurate to obtain a modified polyurethane acrylate prepolymer with urethane bonds in the main chain and acrylate groups at the end.
[0025] The molar ratio of hydroxyl groups in the polycarbonate diol to the hydroxyethyl acrylate is 1:0.8-1.2, and the molar ratio of the isocyanate groups in the isophorone diisocyanate to the total hydroxyl groups in the polycarbonate diol and the hydroxyethyl acrylate is 1.05-1.2:1.
[0026] As a preferred technical solution, the reactive diluent is selected from one or more combinations of isobornyl acrylate, ethoxylated trimethylolpropane triacrylate, and tripropylene glycol diacrylate; the photoinitiator is selected from at least one of 2-hydroxy-2-methyl-1-phenylpropanone and 1-hydroxycyclohexylphenyl ketone.
[0027] As a preferred technical solution, the additives include a leveling agent, a defoamer, and an adhesion promoter. The leveling agent is a polyether-modified polydimethylsiloxane; the defoamer is an acrylate defoamer without organosilicon; and the adhesion promoter is a phosphate-modified acrylate.
[0028] As a preferred technical solution, the adhesive layer is formed by the following steps: after mixing the raw materials and degassing, coating them on the surface of the release layer to form a wet film, bonding them with the polyester substrate layer, and then curing them with ultraviolet light to obtain an adhesive layer with a thickness of 10-40μm and a curing energy of 300-800 mJ / cm².
[0029] As a preferred technical solution, the release layer is a fluorinated release film with a thickness of 25-75 μm;
[0030] The polyester substrate layer is a biaxially oriented polyethylene terephthalate film with a thickness of 25-100 μm, and its surface is corona-treated with a surface tension ≥52 dyne / cm.
[0031] Another object of this application is to provide: a method for preparing the aforementioned alumina aerogel-modified polyester-based high-barrier tape, comprising the following steps:
[0032] (1) Preparation of coupling modified alumina aerogel: Alumina aerogel with an average pore size of 10-50 nm and a specific surface area of 300-600 m² / g is dispersed in anhydrous ethanol, and 10-30% of γ-glycidoxypropyltrimethoxysilane by mass of alumina aerogel is added. The mixture is stirred and reacted at 60-80 °C under nitrogen protection for 6-12 hours. The product is centrifuged, washed three times with anhydrous ethanol, and dried under vacuum at 50 °C to obtain coupling modified alumina aerogel.
[0033] (2) Preparation of modified polyurethane acrylate prepolymer: Polycarbonate diol is dehydrated under vacuum at 100-120℃ for 1 hour, cooled to 60℃, isophorone diisocyanate and dibutyltin dilaurate accounting for 0.05-0.1wt% of the total amount are added, the reaction is carried out for 2-3 hours, and then hydroxyethyl acrylate is added and the reaction is continued for 2-4 hours to obtain the modified polyurethane acrylate prepolymer;
[0034] (3) Prepare adhesive composition: Weigh 60-80 parts of the modified polyurethane acrylate prepolymer obtained in step (2), 5-15 parts of the coupling modified alumina aerogel obtained in step (1), 15-30 parts of reactive diluent, 1-5 parts of photoinitiator and 0.5-2 parts of additives according to the weight, disperse evenly at high speed and then degas under vacuum.
[0035] (4) Coating and curing: The adhesive composition of step (3) is coated on the surface of the release layer and then bonded to the polyester substrate layer. It is cured by ultraviolet light under nitrogen protection. The thickness of the adhesive layer after curing is 10-40 μm and the curing energy is 300-800 mJ / cm², thus obtaining the tape.
[0036] As a preferred technical solution, in step (4), ultraviolet curing is performed using a high-pressure mercury lamp with a main wavelength of 365nm and a curing time of 30-120 seconds.
[0037] Another object of this application is to provide the application of the alumina aerogel modified polyester-based high-barrier tape in the packaging of electronic devices, the protection of flexible display modules or the backsheet of photovoltaic modules.
[0038] As can be seen from the above technical solution, compared with the prior art, the present invention has the following beneficial effects:
[0039] Compared with the prior art, the present invention has the following beneficial effects:
[0040] (1) Significantly improved water and oxygen barrier performance
[0041] This invention covalently grafts alumina aerogel with γ-glycidyl etheroxypropyltrimethoxysilane (KH-560) and uniformly disperses it in a modified polyurethane acrylate prepolymer. The aerogel's three-dimensional porous network structure is used to construct a highly tortuous "maze" barrier pathway. Test results from examples show that the water vapor transmission rate (WVTR) of the tape of this invention is as low as 0.0035-0.025 g / (m²·day), and the oxygen transmission rate (OTR) is as low as 0.07-0.42 cc / (m²·day·atm). This represents a reduction of 2-3 orders of magnitude compared to the pure aerogel system without aerogel (Comparative Example 3, WVTR=12.5), a reduction of 34-243 times compared to the unmodified aerogel system (Comparative Example 1, WVTR=0.85), and a reduction of 7-51 times compared to the sheet-like nano-alumina system (Comparative Example 4, WVTR=0.18). This indicates that KH-560 covalent modification transforms aerogel from a "defect source" into a highly efficient barrier component, with the barrier efficiency of the three-dimensional porous structure being significantly better than that of two-dimensional sheet fillers.
[0042] (2) Excellent optical transparency
[0043] This invention achieves ultra-high barrier properties while maintaining excellent optical transparency. Examples 1-3 exhibit haze of only 1.5%-4.1% and total light transmittance of 86%-91%, while Comparative Example 1 (unmodified aerogel) has a haze as high as 14.5% and a transmittance of only 74%, and Comparative Example 4 (sheet-like nano-alumina) has a haze of 8.5%. This invention breaks the technical prejudice that "adding inorganic fillers inevitably leads to a decrease in transparency." Analysis suggests this is due to the high matching degree between the refractive index of the alumina aerogel (approximately 1.13-1.25) and the polyurethane acrylate matrix (approximately 1.48-1.50), and the reduction of interfacial scattering by the KH-560 graft layer, thus achieving a balance between high barrier properties and high transparency.
[0044] (3) Good flexibility retention
[0045] This invention utilizes KH-560 covalent bonding to form a stable interfacial bond between the aerogel and the polymer matrix, effectively alleviating stress concentration during stretching. Simultaneously, the three-dimensional porous structure of the aerogel itself possesses a certain elastic buffering capacity. Based on a pure aerogel system (Comparative Example 3, elongation at break 210%), the elongation at break retention rates of Examples 1-3 were 81.9%, 92.9%, and 70.5%, respectively, significantly higher than Comparative Example 1 (42.9%), Comparative Example 2 (54.8%), and Comparative Example 4 (64.3%). Typically, high filler content (>5wt%) of inorganic fillers reduces the elongation at break of the adhesive layer by more than 50%. However, this invention, with a filler content of 5-15 parts, still maintains a flexibility retention rate of over 70%, overcoming the technical limitation that "high filler content inevitably leads to a significant decrease in flexibility."
[0046] (4) Excellent resistance to high temperature and high humidity aging
[0047] After aging at 85℃ / 85% RH for 500 hours, the WVTR increase of Examples 1-3 of this invention was only 28.0%-45.7%, while the WVTR increase of Comparative Example 1 (unmodified aerogel) was as high as 629%, and the WVTR increase of Comparative Example 4 (sheet-like nano-alumina) was as high as 189%. The WVTR decay rate of this invention is more than an order of magnitude lower than that of the comparative examples. Analysis suggests that the epoxy groups of KH-560 form covalent bonds with the polyurethane acrylate matrix during UV curing, making the aerogel a covalent bond node in the crosslinking network. This chemical bond has excellent hydrolytic stability under high humidity conditions, thus ensuring the long-term reliability of the tape under harsh environments.
[0048] (5) Good adhesive properties
[0049] The 180° peel strengths of Examples 1-3 of the present invention are 8.2 N / 25mm, 9.1 N / 25mm and 6.9 N / 25mm, respectively, all of which meet the actual application requirements of tapes for electronic packaging. Furthermore, the coating liquid is evenly dispersed without agglomeration, and the surface after coating is smooth without pitting, demonstrating good process adaptability.
[0050] (6) The process is simple and suitable for industrial production.
[0051] The preparation method of this invention is simple, uses readily available raw materials, and can be continuously produced using conventional coating and UV curing equipment. It is highly compatible with existing tape production lines, requiring no additional investment in complex equipment, and has excellent industrial applicability. Furthermore, the tape of this invention can be widely used in fields with stringent requirements for water and oxygen barrier properties, such as electronic device packaging (e.g., OLED peripheral packaging, chip passivation layer protection), flexible display modules (folding screen cover bonding and edge sealing), and photovoltaic modules (backsheet protection and edge sealing). Detailed Implementation
[0052] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0053] All raw materials used in this embodiment are commercially available. Specifically: alumina aerogel was purchased from Xi'an Qiyue Biotechnology Co., Ltd.; γ-glycidyl etheroxypropyltrimethoxysilane (KH-560) was purchased from Tianjin Alta Technology Co., Ltd. (CAS: 2530-83-8); BYK-333 leveling agent and BYK-057 defoamer were purchased from BYK GmbH, Germany; PM-2 adhesion promoter was purchased from Guangzhou Sanwang Chemical Materials Co., Ltd.; dibutyltin dilaurate can be selected from TMG 218 (supplier: Gao Schmidt); fluorine release film can be purchased from Shenzhen Heyu Technology Co., Ltd. FM series; BOPET film is commercially available (such as DuPont Teijin Melinex® series). Other raw materials not specified by supplier are conventional commercially available products in the art.
[0054] Test method:
[0055] Water vapor transmission rate (WVTR): Refer to ASTM F1249, using a MOCON Aquatran instrument, 40℃ / 90% RH.
[0056] Oxygen Transmission Rate (OTR): Refer to ASTM D3985.
[0057] Haze and transmittance: Refer to ASTM D1003, using BYK Hazegard plus.
[0058] 180° peel strength: Tested on stainless steel plate according to GB / T 2792-2014.
[0059] Elongation at break: After the adhesive layer is cured separately, dumbbell-shaped specimens are prepared and stretched at a speed of 50 mm / min.
[0060] Aging resistance test: placed in a constant temperature and humidity chamber at 85℃ / 85% RH for 500 hours.
[0061] Example 1
[0062] A method for preparing an alumina aerogel-modified polyester-based high-barrier adhesive tape includes the following steps:
[0063] (1) Preparation of coupling-modified alumina aerogel
[0064] 10 g of alumina aerogel with a specific surface area of 450 m² / g and an average pore size of 25 nm was ultrasonically dispersed in 200 mL of anhydrous ethanol. 2.5 g of γ-glycidoxypropyltrimethoxysilane (KH-560) was added, nitrogen gas was introduced, and the mixture was heated to 70 °C and stirred for 8 hours. The product was centrifuged, washed three times with anhydrous ethanol, and dried under vacuum at 50 °C for 12 hours to obtain the coupling-modified alumina aerogel.
[0065] (2) Preparation of modified polyurethane acrylate prepolymer: Polycarbonate diol with a number average molecular weight of 2000 was dehydrated under vacuum at 100°C for 1 hour, cooled to 60°C, and isophorone diisocyanate and dibutyltin dilaurate (0.08 wt% of the total mass of polycarbonate diol, isophorone diisocyanate and hydroxyethyl acrylate) were added. The mixture was reacted for 2.5 hours, and then hydroxyethyl acrylate was added and the reaction was continued for 2 hours to obtain the modified polyurethane acrylate prepolymer. The molar ratio of hydroxyl groups in polycarbonate diol to hydroxyethyl acrylate was 1:1, and the molar ratio of isocyanate groups in isophorone diisocyanate to the total hydroxyl groups in polycarbonate diol and hydroxyethyl acrylate was 1.1:1.
[0066] (3) Preparation of adhesive composition: Weigh 70 parts by weight of the modified polyurethane acrylate prepolymer obtained in step (2), 10 parts by weight of the coupling modified alumina aerogel obtained in step (1), 18 parts by weight of isobornyl acrylate, 2.5 parts by weight of 2-hydroxy-2-methyl-1-phenylpropanone, 0.3 parts by weight of leveling agent BYK-333, 0.2 parts by weight of defoamer BYK-057, and 0.5 parts by weight of adhesion promoter PM-2. Disperse at 2000 rpm for 30 minutes using a high-speed disperser, and degas under vacuum (-0.095 MPa) for 30 minutes.
[0067] (4) Coating and Curing: The adhesive composition from step (3) is coated onto the surface of the release layer (fluorinated release film, 50 μm thick), and then bonded to the polyester substrate layer (corona-treated BOPET film, DuPont Teijin Melinex® series, 50 μm thick, surface tension 54 dyne / cm). Curing is performed under nitrogen protection using a high-pressure mercury lamp with a dominant wavelength of 365 nm for 60 seconds, accumulating an energy of 500 mJ / cm². The cured adhesive layer has a thickness of 25 μm. The finished tape is then obtained by winding.
[0068] The corona treatment conditions are as follows: a high-frequency, high-voltage corona treatment machine is used, with an output voltage of 10kV, an operating frequency of 15kHz, a treatment power of 4kW, an electrode-film spacing of 2mm, and a treatment speed of 20m / min. The treated material should be used within 24 hours to ensure surface tension stability.
[0069] Example 2
[0070] A method for preparing an alumina aerogel-modified polyester-based high-barrier adhesive tape includes the following steps:
[0071] (1) Preparation of coupling modified alumina aerogel: Alumina aerogel with an average pore size of 10 nm and a specific surface area of 300 m² / g was dispersed in anhydrous ethanol, and γ-glycidyl oxypropyltrimethoxysilane (10% by weight of alumina aerogel) was added. The mixture was stirred and reacted at 60 °C under nitrogen protection for 6 hours. The product was centrifuged, washed three times with anhydrous ethanol, and dried under vacuum at 50 °C to obtain coupling modified alumina aerogel.
[0072] (2) Preparation of modified polyurethane acrylate prepolymer: Polycarbonate diol with a number average molecular weight of 1000 was dehydrated under vacuum at 100°C for 1 hour, cooled to 60°C, and isophorone diisocyanate and dibutyltin dilaurate (0.05 wt% of the total mass of polycarbonate diol, isophorone diisocyanate and hydroxyethyl acrylate) were added. The mixture was reacted for 2 hours, and then hydroxyethyl acrylate was added and the reaction was continued for another 2 hours to obtain the modified polyurethane acrylate prepolymer. The hydroxyl molar ratio of polycarbonate diol to hydroxyethyl acrylate was 1:0.8, and the molar ratio of isocyanate groups of isophorone diisocyanate to the total hydroxyl groups of polycarbonate diol and hydroxyethyl acrylate was 1.05:1.
[0073] (3) Preparation of adhesive composition: Weigh 80 parts of the modified polyurethane acrylate prepolymer obtained in step (2), 5 parts of the coupling modified alumina aerogel obtained in step (1), 15 parts of ethoxylated trimethylolpropane triacrylate, 1 part of 1-hydroxycyclohexylphenyl ketone, 0.2 parts of leveling agent BYK-333, 0.1 parts of defoamer BYK-057, and 0.2 parts of adhesion promoter PM-2. Disperse the mixture at 2000 rpm for 30 minutes using a high-speed disperser and degas it under vacuum (-0.095 MPa) for 30 minutes.
[0074] (4) Coating and Curing: The adhesive composition from step (3) is coated onto the surface of the release layer (fluorinated release film, 25 μm thick), and then bonded to the polyester substrate layer (corona-treated BOPET film, 25 μm thick, surface tension 56 dyne / cm). Ultraviolet curing is performed under nitrogen protection using a high-pressure mercury lamp with a dominant wavelength of 365 nm and a curing time of 30 seconds. The cured adhesive layer has a thickness of 10 μm and a curing energy of 300 mJ / cm², yielding the tape.
[0075] The corona treatment conditions are as follows: a high-frequency, high-voltage corona treatment machine is used, with an output voltage of 10kV, an operating frequency of 15kHz, a treatment power of 4kW, an electrode-film spacing of 2mm, and a treatment speed of 20m / min. The treated material should be used within 24 hours to ensure surface tension stability.
[0076] Example 3
[0077] A method for preparing an alumina aerogel-modified polyester-based high-barrier adhesive tape includes the following steps:
[0078] (1) Preparation of coupling modified alumina aerogel: Alumina aerogel with an average pore size of 50 nm and a specific surface area of 600 m² / g was dispersed in anhydrous ethanol, and γ-glycidyl oxypropyltrimethoxysilane (30% by weight of alumina aerogel) was added. The mixture was stirred and reacted at 80 °C under nitrogen protection for 12 hours. The product was centrifuged, washed three times with anhydrous ethanol, and dried under vacuum at 50 °C to obtain coupling modified alumina aerogel.
[0079] (2) Preparation of modified polyurethane acrylate prepolymer: Polycarbonate diol with a number average molecular weight of 3000 was dehydrated under vacuum at 120°C for 1 hour, cooled to 60°C, and isophorone diisocyanate and dibutyltin dilaurate (0.1 wt% of the total mass of polycarbonate diol, isophorone diisocyanate and hydroxyethyl acrylate) were added. The mixture was reacted for 3 hours, and then hydroxyethyl acrylate was added and the reaction was continued for 4 hours to obtain the modified polyurethane acrylate prepolymer. The molar ratio of hydroxyl groups in polycarbonate diol to hydroxyethyl acrylate was 1:1.2, and the molar ratio of isocyanate groups in isophorone diisocyanate to the total hydroxyl groups in polycarbonate diol and hydroxyethyl acrylate was 1.2:1.
[0080] (3) Preparation of adhesive composition: Weigh 80 parts of the modified polyurethane acrylate prepolymer obtained in step (2), 15 parts of the coupling modified alumina aerogel obtained in step (1), 30 parts of tripropylene glycol diacrylate, 5 parts of 1-hydroxycyclohexylphenyl ketone, 0.8 parts of leveling agent BYK-333, 0.4 parts of defoamer BYK-057, and 0.8 parts of adhesion promoter PM-2 according to the weight ratio. Disperse the mixture at 2000 rpm for 30 minutes using a high-speed disperser and degas it under vacuum (-0.095 MPa) for 30 minutes.
[0081] (4) Coating and Curing: The adhesive composition from step (3) is coated onto the surface of the release layer (fluorinated release film, 75 μm thick), and then bonded to the polyester substrate layer (corona-treated BOPET film, 100 μm thick, surface tension 54 dyne / cm). Ultraviolet curing is performed under nitrogen protection using a high-pressure mercury lamp with a dominant wavelength of 365 nm and a curing time of 120 seconds. The cured adhesive layer has a thickness of 40 μm and a curing energy of 800 mJ / cm², yielding the tape.
[0082] The corona treatment conditions are as follows: a high-frequency, high-voltage corona treatment machine is used, with an output voltage of 10kV, an operating frequency of 15kHz, a treatment power of 4kW, an electrode-film spacing of 2mm, and a treatment speed of 20m / min. The treated material should be used within 24 hours to ensure surface tension stability.
[0083] Comparative Example 1 (using unmodified alumina aerogel)
[0084] The only difference from Example 1 is that the alumina aerogel is not modified by KH-560 and is added directly as is.
[0085] Phenomenon: The coating liquid showed obvious sedimentation and particle agglomeration, and the surface after coating had visible pits.
[0086] Comparative Example 2 (using KH-550 modified alumina aerogel)
[0087] The difference from Example 1 is that the coupling agent was changed to γ-aminopropyltriethoxysilane (KH-550).
[0088] Comparative Example 3 (Aerogel-free)
[0089] Only prepolymers and reactive diluents are used; no aerogel is added.
[0090] Comparative Example 4 (using sheet-like nano-alumina, not aerogel)
[0091] The coupling-modified alumina aerogel was replaced with the same mass of KH-560 modified sheet-like nano-alumina (average particle size 100 nm, thickness 10 nm).
[0092] Performance testing
[0093] Adhesive tape samples were prepared according to the preparation methods of Examples 1-3 and Comparative Examples 1-4. The water vapor transmission rate (WVTR), oxygen transmission rate (OTR), haze, total light transmittance, elongation at break, 180° peel strength, and WVTR after aging at 85°C / 85%RH for 500 hours were tested for each sample. The results are shown in Tables 1 and 2.
[0094] Table 1 Comparison of barrier properties and optical properties
[0095] project WVTR(g / (m²·day)) OTR(cc / (m²·day·atm)) Haze (%) Total light transmittance (%) Example 1 0.008 0.15 2.3 89 Example 2 0.025 0.42 1.5 91 Example 3 0.0035 0.07 4.1 86 Comparative Example 1 0.85 8.3 14.5 74 Comparative Example 2 0.42 - 11.8 - Comparative Example 3 12.5 48 0.6 - Comparative Example 4 0.18 - 8.5 -
[0096] Note: "-" indicates that no detection was performed.
[0097] Results Analysis: Table 1 shows that the WVTR of Examples 1-3 was 0.0035-0.025 g / (m²·day), which is 2-3 orders of magnitude lower than that of Comparative Example 3 (pure gel system, 12.5), 34-243 times lower than that of Comparative Example 1 (unmodified aerogel, 0.85), and 7-51 times lower than that of Comparative Example 4 (sheet alumina, 0.18). This indicates that KH-560 covalent modification transforms the aerogel from a "defect source" into a highly efficient barrier component, and the barrier efficiency of the three-dimensional porous structure is significantly better than that of the two-dimensional sheet filler.
[0098] In terms of optical performance, the haze of Examples 1-3 is only 1.5%-4.1%, and the transmittance is 86%-91%, while the haze of Comparative Example 1 is as high as 14.5% and that of Comparative Example 4 is 8.5%. This invention breaks the technical prejudice that "adding inorganic materials will inevitably lead to a decrease in transparency" and achieves both high barrier properties and high transparency.
[0099] Table 2 Comparison of Mechanical Properties and Aging Resistance
[0100] project Elongation at break (%) Elongation at break retention rate (%) 180° peel strength (N / 25mm) WVTR after aging (g / (m²·day)) WVTR increase (%) Example 1 172 81.9 8.2 0.011 37.5 Example 2 195 92.9 9.1 0.032 28.0 Example 3 148 70.5 6.9 0.0051 45.7 Comparative Example 1 90 42.9 — 6.2 629 Comparative Example 2 115 54.8 — 1.5 257 Comparative Example 3 210 benchmark — — — Comparative Example 4 135 64.3 — 0.52 189
[0101] Note: WVTR increase = (WVTR after aging - Initial WVTR) / Initial WVTR × 100%
[0102] Results analysis:
[0103] Regarding flexibility, the elongation at break retention rates of Examples 1-3 (based on Comparative Example 3) were 70.5%-92.9%, significantly higher than Comparative Example 1 (42.9%), Comparative Example 2 (54.8%), and Comparative Example 4 (64.3%). This indicates that covalent bonding alleviated stress concentration, and the porous structure of the aerogel provided elastic buffering.
[0104] Regarding aging resistance, after aging at 85℃ / 85%RH for 500 hours, the WVTR of Examples 1-3 increased by 28%-45.7%, while Comparative Example 1 reached as high as 629% and Comparative Example 4 reached as high as 189%, with the decay rate decreasing by more than an order of magnitude. This indicates that the covalently bonded interface formed by KH-560 has excellent hydrolytic stability.
[0105] Regarding peel strength, Examples 1-3 show 6.9-9.1 N / 25mm, which meets the requirements for practical applications.
[0106] In summary, Examples 1-3 are significantly superior to the comparative examples in terms of barrier properties, optics, flexibility, and aging resistance, achieving a performance balance that is impossible to achieve with existing technologies.
[0107] The various embodiments in this specification are described in a progressive manner, with each embodiment focusing on the differences from other embodiments. The same or similar parts between the various embodiments can be referred to each other.
[0108] The above description of the disclosed embodiments enables those skilled in the art to make or use the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. An alumina aerogel-modified polyester-based high-barrier tape, characterized in that, The tape comprises a release layer, an adhesive layer, and a polyester substrate layer stacked in sequence; The adhesive layer is prepared from raw materials comprising the following parts by weight: 60-80 parts of modified polyurethane acrylate prepolymer; 5-15 parts of coupling-modified alumina aerogel; 15-30 parts of reactive diluent; 1-5 parts of photoinitiator; Additives: 0.5-2 parts; The coupled-modified alumina aerogel is prepared by grafting γ-glycidyl etheroxypropyltrimethoxysilane onto alumina aerogel via a sol-gel surface reaction. The alumina aerogel has an average pore size of 10-50 nm and a specific surface area of 300-600 m². 2 / g.
2. The alumina aerogel-modified polyester-based high-barrier tape according to claim 1, characterized in that, The coupling-modified alumina aerogel was prepared by the following method: alumina aerogel was dispersed in anhydrous ethanol, and 10-30% by weight of γ-glycidoxypropyltrimethoxysilane was added. The mixture was stirred and reacted at 60-80℃ for 6-12 hours under nitrogen protection. After centrifugation, washing, and vacuum drying, the coupling-modified alumina aerogel was obtained.
3. The alumina aerogel-modified polyester-based high-barrier tape according to claim 1, characterized in that, The modified polyurethane acrylate prepolymer was prepared by the following method: polycarbonate diol, isophorone diisocyanate and hydroxyethyl acrylate with a number average molecular weight of 1000-3000 were reacted in the presence of dibutyltin dilaurate catalyst to obtain a modified polyurethane acrylate prepolymer with urethane bonds in the main chain and acrylate groups at the end. The molar ratio of hydroxyl groups in the polycarbonate diol to the hydroxyethyl acrylate is 1:0.8-1.2, and the molar ratio of the isocyanate groups in the isophorone diisocyanate to the total hydroxyl groups in the polycarbonate diol and the hydroxyethyl acrylate is 1.05-1.2:
1.
4. The alumina aerogel-modified polyester-based high-barrier tape according to claim 1, characterized in that, The reactive diluent is selected from one or more combinations of isobornyl acrylate, ethoxylated trimethylolpropane triacrylate, and dipropylene glycol diacrylate; the photoinitiator is selected from at least one of 2-hydroxy-2-methyl-1-phenylpropanone and 1-hydroxycyclohexylphenyl ketone.
5. The alumina aerogel-modified polyester-based high-barrier tape according to claim 1, characterized in that, The additives include a leveling agent, a defoamer, and an adhesion promoter. The leveling agent is a polyether-modified polydimethylsiloxane; the defoamer is an acrylate defoamer without organosilicon; and the adhesion promoter is a phosphate-modified acrylate.
6. The alumina aerogel-modified polyester-based high-barrier tape according to claim 1, characterized in that, The adhesive layer is formed by the following steps: after mixing the raw materials and degassing, the mixture is coated on the surface of the release layer to form a wet film, which is then bonded to the polyester substrate layer and cured by ultraviolet light to obtain an adhesive layer with a thickness of 10-40 μm and a curing energy of 300-800 mJ / cm².
7. The alumina aerogel-modified polyester-based high-barrier tape according to claim 1, characterized in that, The release layer is a fluorinated release film with a thickness of 25-75 μm; The polyester substrate layer is a biaxially oriented polyethylene terephthalate film with a thickness of 25-100 μm, and its surface is corona-treated with a surface tension ≥52 dyne / cm.
8. A method for preparing an alumina aerogel-modified polyester-based high-barrier tape according to any one of claims 1-7, characterized in that, Includes the following steps: (1) Preparation of coupling modified alumina aerogel: Alumina aerogel with an average pore size of 10-50 nm and a specific surface area of 300-600 m² / g is dispersed in anhydrous ethanol, and 10-30% of γ-glycidoxypropyltrimethoxysilane by mass of alumina aerogel is added. The mixture is stirred and reacted at 60-80 °C under nitrogen protection for 6-12 hours. The product is centrifuged, washed three times with anhydrous ethanol, and dried under vacuum at 50 °C to obtain coupling modified alumina aerogel. (2) Preparation of modified polyurethane acrylate prepolymer: Polycarbonate diol is dehydrated under vacuum at 100-120℃ for 1 hour, cooled to 60℃, isophorone diisocyanate and dibutyltin dilaurate accounting for 0.05-0.1wt% of the total amount are added, the reaction is carried out for 2-3 hours, and then hydroxyethyl acrylate is added and the reaction is continued for 2-4 hours to obtain the modified polyurethane acrylate prepolymer; (3) Prepare adhesive composition: Weigh 60-80 parts of the modified polyurethane acrylate prepolymer obtained in step (2), 5-15 parts of the coupling modified alumina aerogel obtained in step (1), 15-30 parts of reactive diluent, 1-5 parts of photoinitiator and 0.5-2 parts of additives according to the weight, disperse evenly at high speed and then degas under vacuum. (4) Coating and curing: The adhesive composition of step (3) is coated on the surface of the release layer and then bonded to the polyester substrate layer. It is cured by ultraviolet light under nitrogen protection. The thickness of the adhesive layer after curing is 10-40 μm and the curing energy is 300-800 mJ / cm², thus obtaining the tape.
9. The preparation method according to claim 8, characterized in that, In step (4), ultraviolet curing is performed using a high-pressure mercury lamp with a main wavelength of 365nm and a curing time of 30-120 seconds.
10. The application of the alumina aerogel modified polyester-based high-barrier tape according to any one of claims 1-7 in the packaging of electronic devices, the protection of flexible display modules or the backsheet of photovoltaic modules.